Role of diacerein in pain intensity and functional status in patients with knee osteoarthritis - Kasjmir, Yoga I; Imelda, F; Erawati, L (Indonesian Rheumatology Association, 2010)
Background: Infl ammation is an important mechanism in the pathogenesis of osteoarthritis (OA). Proinfl ammatory mediators, especially interleukin-1Î² (IL-1Î²), play a signifi cant role in the occurrence of joint infl ammation, which lead to pain and limitation of daily activities. As an antiâIL-1Î², diacerein is therefore have potency to reduce pain and improve functional status of OA patients.Objective: To evaluate the role of diacerein in pain intensity and functional status of knee OA patients. Methods: This is a pre-post study without control group using consecutive sampling conducted at rheumatology outpatient clinic at the Cipto Mangunkusumo General Hospital, Jakarta from January until May 2006. At the fi rst visit, all patients underwentassessment of pain intensity (using visual analog scale (VAS)) and functional status (Lequesne algofunctional index) to obtain baseline data. We also performed kneeradiograph examination to evaluate joint damage basedon the Kellgren-Lawrence classifi cation. Measurement of IL-1Î² level in synovial fl uid was performed using enzyme-linked immunosorbent assay, with a minimum detectable value of 3.9 pg/mL. Diacerein wasadministered with a dose of 50 mg, given orally twice a day for 2 months. Follow-ups were done in the fi rst, second, and eighth week after the administration of diacerein. In the eighth week we repeated the measurement of IL-1Î² level.Results: Thirty three patients were enrolled in this study, most (78.8%) of them were female. The majority (81.8%) belong to the 50- to 70-year-old age group. More than half of the patients (54.5%) had detectable IL-1Î² level. The median baseline VAS score was 65.00 (range 25â100) while the median baseline Lequesne score was 11.00 (range 1.5â21.0). The statistical analysis showed a signifi cant decrease in VAS at the fi rst (p = 0.000), second(p = 0.000), and eighth week (p = 0.000). Lequesne index score was also decrease signifi cantly at the fi rst (p =0.000), second (p = 0.000), and eighth week (p = 0.000)of treatment. We found no signifi cant correlation of IL-1Î² level with VAS and Lequesne algofunctional index scores.Conclusions: Among the patients in this study, there were signifi cant decrease in pain intensity and disabilityafter the administration of diacerein.